PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PENGAWASAN DAN HUMAN RELATION TERHADAP KINERJA KARYAWAN PADA PT. INDAH CARGO PEKANBARU - Dwijayati, Putri; Ningsih, Dewita Suryati; Rokhmawati, Andewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to exemine the effect of transformational leadership, supervision and human relation to employee performance of PT. Indah Cargo Pekanbaru. The population in this study were employees’ of PT. Indah Cargo Pekanbaru as many as 168 people. The sampling was done with slovin formula thus obtained sample of 62 people. Analysis of the data was descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18.00. The test results have shown that transformational leadership, supervision, and human relations simultaneously and parstially have significant effect on the performance of employees at Indah Cargo Pekanbaru. Companies need to improve employee performance such as creating a harmonious communication within the company that is the communication between superiors and subordinates and among employees. This can be done by making regulations to complete the work by means of flocking. Therefore employees will communicate with each other, but it will also oversee leadership and facilitate communication between subordinates to superiors. With the implementation of the terms of expected employees will be motivated to achieve corporate goals to be able to survive amid competition from other freight brokerage company.Keyword : Transformational Leadership, Supervision, Human Relation and Performance